Effects of LPS on the accumulation of lipid droplets, proliferation, and steroidogenesis in goat luteinized granulosa cells. Issue 7 (1st April 2019) - Maoduo, Zhang; Hao, Yu; Wei, Wang; Feng, Wang; Dagan, Mao
Abstract: Lipopolysaccharide (LPS) can cause ovarian dysfunction and infertility in mammals. The purpose of this study was to investigate the effects of LPS on the accumulation of lipid droplets (LDs), proliferation, and steroidogenesis in goat luteinized granulosa cells (LGCs). GCs isolated from the ovarian follicles were spontaneously luteinized under media with fetal bovine serum, resulting in increased progesterone and shifted shape from spherical to star with multiple prolongations. Then, LGCs were treated with LPS (0‐10 μg/mL) for 0‐48 hours. Oil Red O staining was performed to observe LDs accumulation and commercial kit was applied to detect intracellular triglyceride (TG) content. The cell proliferation were detected by cell counting kit‐8. Expressions of cell‐cycle–related genes were determined by real‐time polymerase chain reaction. Estradiol (E2 ) and progesterone (P4 ) from cell supernatants were determined by enzyme‐linked immunosorbent assay, and expressions of STAR, P450scc, 3β‐hydroxysteroid dehydrogenase (3β‐HSD) and CYP19A1 were detected by Western blot. Results showed that LPS treatment significantly increased LDs accumulation after 24 hours, and 5 μg/mL LPS increased TG content ( P  < 0.05). LPS treatment for 24 hours stimulated the LGCs activities ( P <0.05), which was confirmed by the increases in the expressions of proliferating cell nuclear antigen (PCNA), cyclinB1 and cyclinD1, while 48 hours treatment had no effect. LPS treatment suppressed E2 and P4 output of LGCs ( P  < 0.05). Western blot results showed that 10 μg/mL LPS decreased the protein expression of 3β‐HSD in LGCs ( P  < 0.05). In conclusion, LPS increased LDs accumulation and cell proliferation, and LPS‐mediated P4 reduction could be attributed to the decreased 3β‐HSD protein expression, which provide new information for the regulation of ovarian function in goats. HIGHLIGHTS: LPS increased the content of lipid droplet in goat luteinized granulosa cells. LPS promoted the proliferation of goat luteinized granulosa cells after treatment for 24 hours. LPS suppressed P4 and E2 output which can be attributed to the decreased 3β‐HSD protein expression.